1993
DOI: 10.1111/j.1600-0714.1993.tb00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral candidiasis established in the sialoadenectomised rat

Abstract: Xerostomia provoked in rats by surgical removal of the major salivary glands favoured the development of oral candidiasis. After 32 weeks of inoculation, 20% of normal and 70% of xerostomic rats showed candidal infection on the tongue but only in xerostomic rats did candidiasis affect the pharyngeal aspect of the tongue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
1
17
1
Order By: Relevance
“…The relationship between xerostomia and oral candidiasis was investigated in the monkey model (133), as described earlier in this review. Jorge et al (83) used Wistar rats to further study this phenomenon. They rendered 20 Wistar rats xerostomic by surgical removal of the major salivary glands (parotid, sublingual, and submandibular) and orally inoculated them with C. albicans three times a week for 32 weeks.…”
Section: Wistar Rat Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between xerostomia and oral candidiasis was investigated in the monkey model (133), as described earlier in this review. Jorge et al (83) used Wistar rats to further study this phenomenon. They rendered 20 Wistar rats xerostomic by surgical removal of the major salivary glands (parotid, sublingual, and submandibular) and orally inoculated them with C. albicans three times a week for 32 weeks.…”
Section: Wistar Rat Modelmentioning
confidence: 99%
“…Other predisposing factors for oral candidiasis that have come under scrutiny in a number of animal models include broad-spectrum antibiotic therapy (5,82,(155)(156)(157), carbohydrate-rich diets (66,154,155), topical use of corticosteroids (47), corticosteroid inhalation (28), trauma (131), iron deficiency (147,185), diabetes (51), xerostomia (1,83,84,119,133), decrease in CD4 ϩ T-cell counts and phagocytic function (31,32), defective T-cell function (16), and immunosuppressive therapy (27,172). Undoubtedly, these studies have helped us to understand the etiology of oral candidiasis and the development of the management protocols that are currently prevalent.…”
Section: Need For and Clinical Relevance Of Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long term of smoking will change salivary flow rates and pH of saliva [2,6,15,24,25]. The change of salivary flow rates has important role in pathogenesis of candidiasis [17,21,22]. Smoking also causes decreasing the antibody in saliva, and affects the amount of microorganism in saliva.…”
Section: Resultsmentioning
confidence: 99%
“…Research done by Navazesh et al (1995) showed relation that inversely proportional between salivary flow rate and amount of candida in saliva [21,22]. The research done by Torrest et al (2002) also proved that subject with low salivary flow rate has higher amount of candida [23].…”
Section: Introductionmentioning
confidence: 99%